2018
DOI: 10.1002/jcp.26908
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐874 alleviates renal injury and inflammatory response in diabetic nephropathy through targeting toll‐like receptor‐4

Abstract: Diabetic nephropathy (DN) is a kind of diabetic complication with capillary damage, and its pathogenesis remains obscure. Recently, microRNAs have been identified as diagnostic biomarkers in various diseases including DN. Toll-like receptor 4 (TLR4) contributes to inflammation, and it has been implicated in diabetes pathophysiology. This study was designed to investigate the role of miR-874 and TLR4 in a streptozotocin (STZ)-induced DN rat model and glucose-induced mouse podocyte model. In the current study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 34 publications
1
42
2
Order By: Relevance
“…Recent studies have revealed that miRNAs participate in the development and progression of DR and are involved in multiple pathogenesis of DR [14][15][16]. We found a site where miR-874 bound to the NF-κB p65 by the prediction on a bioinformatics website, and the down-regulation of miR-874 expression in rats with myocardial ischemia reperfusion injury exerted an inhibitory effect on inflammation and injury [17,18]. However, we did not found the relationship between miR-874 and DR.…”
Section: Introductioncontrasting
confidence: 58%
“…Recent studies have revealed that miRNAs participate in the development and progression of DR and are involved in multiple pathogenesis of DR [14][15][16]. We found a site where miR-874 bound to the NF-κB p65 by the prediction on a bioinformatics website, and the down-regulation of miR-874 expression in rats with myocardial ischemia reperfusion injury exerted an inhibitory effect on inflammation and injury [17,18]. However, we did not found the relationship between miR-874 and DR.…”
Section: Introductioncontrasting
confidence: 58%
“…MicroRNA-195 facilitated apoptosis of podocytes treated with high-glucose through elevating caspase activity for BCL2 insufficiency [29]. MiR-874 relieved podocyte injury in DN via regulating TLR4 expression [30]. MiR-320a facilitated DN development via targeting MafB and relieving Nephrin and Gpx3 [31].…”
Section: Discussionmentioning
confidence: 99%
“…In DN patients, restoration of miR-374a expression in renal tubular epithelial cells prevented the inflammatory response (Yang et al, 2018b). Similarly, miR-874 negatively regulates the expression of Toll-like receptor-4 (Tlr4), and thus prevents the secretion of pro-inflammatory cytokines in DN mice (Yao et al, 2018). Another anti-inflammatory miRNA is the miR-455-3p that negatively regulates the expression of coil-containing protein kinase 2 (ROCK2), and consequently reduced the inflammatory cytokines and fibrosis markers in a human kidney cell line (Wu et al, 2018).…”
Section: Mirnas In Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Similar to MALAT-1, pro-inflammatory lncRNA, GM6135 increases the expression of Tlr4, by competitive binding to miR-203-3p, thus further activates the secretion of pro-inflammatory cytokines in DN mice (Ji et al, 2019). Interestingly, miR-874 also negatively regulates the Tlr4 gene expression (Yao et al, 2018). Thus further works are needed to determine whether lncRNA GM6135 could interact with miR-874 and elevates TLR4 expression.…”
Section: Lncrna-mirna Interactions In Oxidative Stress and Inflammationmentioning
confidence: 99%